Tente outra vez: o anteprojeto de reforma da lei de direitos autorais, sua compatibilidade na sociedade da informação e a espera pela reforma que nunca chega - Liguori Filho, Carlos Augusto (2016)
The development of new information technologies and the popularization of the Internet as the main form of communication of the contemporary society had a direct impact in cultural production, one of the main objects of Copyright Law. These technologies changed and facilitated the way one creates, reproduces and shares intellectual works. Nevertheless, this is applicable both to legal and illegal uses of copyrighted material. The current Brazilian Copyright Act (Lei nº 9.610/98), formulated shortly before the digital era, is anachronistic in relation to those modifications, being insufficient to prevent illegal uses of copyrighted works, and inflexible in relation to some uses that are only feasible in the digital context, but are directly related to the constitutional right to access to culture. With this diagnostic in mind, the Ministry of Culture drafted and put into public consultation a Copyright Act Reformation Bill, aiming to adequate the regulatory system to this new context. The public consultation was undertaken in 2010, and the consolidated bill was revised in 2011. By the end of that year, the bill was shelved. Both consolidated texts had the participation of multiple stakeholders. The main objective of this work is to evaluate the compatibility of the bill in the context of the information society. In order to do this, we first identified the main functions of Copyright law: the promotional function (stimulate the cultural production) and the social function (ensure access to culture). With that in mind, we analyzed the impact of new information technologies in relation to (i) the support in which the copyrighted work is affixed; (ii) the medium in which the works are shared; and (iii) the new forms of creation that are enabled through digital technologies. After that, we established an overview of the regulatory reactions to those impacts. We then evaluated how those reactions influenced the fulfillment of the two aforementioned functions of Copyright. After this diagnostic, we were able to analyze and evaluate the Copyright Act Reformation Bill in relation to the information society. As a conclusion, even if the bill was not entirely adequate, it represented a huge step forward in relation to the current Copyright Act. Unfortunately, the fact that the bill was shelved represented a huge missed opportunity and a step back in relation the adaptation of the Copyright system in the digital era.